2001
DOI: 10.1046/j.1439-0272.2001.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various cryopreservation media and freezing-thawing on the morphology of rat testicular biopsies

Abstract: Currently, testicular sperm extraction is successfully combined with intracytoplasmic sperm injection into the oocyte (ICSI). Several pieces of a testicular biopsy can be frozen and thawed until the ICSI attempt. In this study, the effects of freezing-thawing on the morphology of rat testicular biopsies stored in different cryopreservation media were analysed. Each cryopreservation medium contained glycerol and/or dimethyl sulfoxide (DMSO) as cryoprotectants. In general, both glycerol and DMSO, when applied at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
2
14
0
4
Order By: Relevance
“…With sucrose as CPA, testicular seminiferous tubule basal parts were seriously injured. DMSO had been found to be a more suitable CPA than ethylene glycol (EG) for immature mouse and rat testis tissue (Goossens et al, 2008;Jezek et al, 2001). Milazzo et al (2008) reported that freezing testes with DMSO maintained not only immature testicular tissue architecture but also the viability of testicular cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With sucrose as CPA, testicular seminiferous tubule basal parts were seriously injured. DMSO had been found to be a more suitable CPA than ethylene glycol (EG) for immature mouse and rat testis tissue (Goossens et al, 2008;Jezek et al, 2001). Milazzo et al (2008) reported that freezing testes with DMSO maintained not only immature testicular tissue architecture but also the viability of testicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Keros et al (2005) compared the DMSO and sucrose regarding their testicular tissue cryopreservation effect and showed that 10 % DMSO had the best protection effect and 6 % sucrose had the worst protection effect. DMSO has been found to be a more suitable CPA than ethylene glycol (EG) for immature mouse and rat testis tissue (Goossens et al, 2008;Jezek et al, 2001). Yildiz et al (2013) indicated that neonatal mouse testes in DMSO had a higher rate of tissue survival than in PrOH and glycerol after graft.…”
Section: Introductionmentioning
confidence: 99%
“…Later, other detailed studies comparing multiple protocols showed high cell viability with programmed slow-freezing of immature mouse testis tissue using 1.5M DMSO as a cryoprotectant (Milazzo et al, 2008;Traverse et al, 2011). DMSO has also been found to be a more suitable cryoprotective agent than ethylene glycol for immature mouse and rat testis tissue (Goossens et al, 2008;Jezek, 2001). Shinohara et al (2002) reported the birth of mouse offspring from sperm retrieved from cryopreserved pre-pubertal testis tissue with DMSO after transplantation under tunica albuginea of the recipient testes (Shinohara et al, 2002).…”
Section: Current Trends In Testis Tissue Cryopreservationmentioning
confidence: 99%
“…Cryopreservation of testicular tissue has been studied since about ten years in animals (Jezek et al, 2001;Jahnukainen et al, 2007;Milazzo et al, 2008;Zeng et al, 2009;Abrishami et al, 2010;Milazzo et al, 2010;Curaba et al, 2011) and human (Bahadur and Ralph, 1999;Bahadur et al, 2000;Guerin, 2005;Revel and Mejia, 2010). It is the only available solution for pre-pubertal boys who must receive a gonadotoxic treatment (eg.…”
Section: Cryopreservation Of Testicular Tissuementioning
confidence: 99%